13R,20-Dihydroxydocosahexaenoic Acid, a Novel Dihydroxy- DHA Derivative, Inhibits Breast Cancer Stemness through Regulation of the Stat3/IL-6 Signaling Pathway by Inducing ROS Production - Lifang Wang; Hack Sun Choi; Binna Lee; Jong Hyun Choi; Yong-Suk Jang; Jeong-Woo Seo (Antioxidants, 2021)
Breast cancer is a major health problem worldwide. Cancer stem cells (CSCs) are known to mediate breast cancer metastasis and recurrence and are therefore a promising therapeutic target. In this study, we investigated the anti-inflammatory effect of 13R,20-dihydroxydocosahexaenoic acid (13R,20-diHDHA), a novel dihydroxy-DHA derivative, which was synthesized through an enzymatic reaction using cyanobacterial lipoxygenase. We found that 13R,20-diHDHA reduced the macrophage secretion of the inflammatory cytokines, IL-6 and TNF-α, and thus appeared to have anti-inflammatory effects. As the inflammatory tumor microenvironment is largely devoted to supporting the cancer stemness of breast cancer cells, we investigated the effect of 13R,20-diHDHA on breast cancer stemness. Indeed, 13R,20-diHDHA effectively inhibited breast cancer stemness, as evidenced by its ability to dose-dependently inhibit the mammospheres formation, colony formation, migration, and invasion of breast CSCs. 13R,20-diHDHA reduced the populations of CD44high/CD24low and aldehyde dehydrogenase (ALDH)-positive cells and the expression levels of the cancer stemness-related self-renewal genes, Nanog, Sox2, Oct4, c-Myc, and CD44. 13R,20-diHDHA increased reactive oxygen species (ROS) production, and the generated ROS reduced the phosphorylation of nuclear signal transducer and activator of transcription 3 (Stat3) and the secretion of IL-6 by mammospheres. These data collectively suggest that 13R,20-diHDHA inhibits breast cancer stemness through ROS production and downstream regulation of Stat3/IL-6 signaling, and thus might be developed as an anti-cancer agent acting against CSCs.